Small Cell Lung Cancer Accompanied by Tonsillar Metastasis and Anti-Hu Antibody-Associated Paraneoplastic Neuropathy: A Rare Case Report With Long-Term Survival. Issue 50 (December 2015) - Ni, Jianjiao; Weng, Linqian; Liu, Mingsheng; Yang, Hua; Wang, Yingyi
Abstract : Abstract: Tonsillar metastatic small cell lung cancer (SCLC) is rare, while anti-Hu antibodies are frequently found in SCLC. A 66-year-old man was admitted to our hospital with painful dysesthesia and muscle weakness in the distal extremities for over 1 year, progressive dysphagia for over 1 month, and severe cough and dyspnea for over 1 week. He was diagnosed with SCLC accompanied by tonsillar metastasis and anti-Hu antibody-associated paraneoplastic sensory neuropathy (PSN). The patient tolerated 6 cycles of sequential chemoradiotherapy and gradually recovered. The patient's disease remained in remission 2 years after the diagnosis with a remarkable reduction of tumor burden and a persisting high titer of anti-Hu antibodies. To our knowledge, this is the first case of tonsillar metastatic SCLC accompanied by anti-Hu antibody-associated PSN, whereby the anticancer immune response was presumed to play a vital role in disease control. Unilateral tonsillar metastasis of SCLC accompanied by anti-Hu antibody-associated PSN can occur and in certain circumstances, may have a favorable prognosis.